Instructional Video Media as a Solution for Teaching Wheel Alignment (Spooring) Practices in Vocational High Schools - Aziz Cahya Pradana; Martubi Martubi (Teknodika, 2026)
Vocational education prepares students with industry-relevant technical competencies through practice-based learning. In automotive vocational programs, wheel alignment is a critical skill involving the adjustment of camber, caster, and toe angles to ensure vehicle stability and safety. However, the implementation of wheel alignment practice in vocational high schools often faces constraints such as limited workshop facilities, restricted practice time, and an imbalance between the number of students and available equipment. These limitations frequently result in teacher-centered demonstrations with limited opportunities for students to observe and practice procedures, which may hinder the development of procedural understanding. This study aims to examine the effectiveness of instructional video media in improving students’ learning outcomes in wheel alignment competency. A quasi-experimental method with a one-group pretest–posttest design was employed involving 36 twelfth-grade students at SMKN 1 Jetis. Data were collected through observation, questionnaires, and practical performance tests. The paired sample t-test results showed a significant improvement in student learning outcomes, with the mean score increasing from 63.08 in the pretest to 84.62 in the posttest (p < 0.05). These findings indicate that instructional video media effectively enhance students’ procedural understanding and support their readiness for workshop practice in vocational education.